Semi-automated Rapid Quantification of Brain Vessel Density Utilizing Fluorescent Microscopy - Bohn, Kaci A. (J Neurosci Methods, 2016)
BACKGROUND: Measurement of vascular density has significant value in characterizing healthy and diseased tissue, particularly in brain where vascular density varies among regions. Further, an understanding of brain vessel size helps distinguish between capillaries and larger vessels like arterioles and venules. Unfortunately, few cutting edge methodologies are available to laboratories to rapidly quantify vessel density. NEW METHOD: We developed a rapid microscopic method, which quantifies the numbers and diameters of blood vessels in brain. Utilizing this method we characterized vascular density of five brain regions in both mice and rats, in two tumor models, using three tracers. RESULTS: We observed the number of sections/mm(2) in various brain regions: genu of corpus callosum 161 ± 7, hippocampus 266 ± 18, superior colliculus 300 ± 24, frontal cortex 391 ± 55, and inferior colliculus 692 ± 18 (n=5 animals). Regional brain data were not significantly different between species (p>0.05) or when using different tracers (70kDa and 2000kDa Texas Red; p>0.05). Vascular density decreased (62–79%) in preclinical brain metastases but increased (62%) a rat glioma model. COMPARISON WITH EXISTING METHODS: Our values were similar (p>0.05) to published literature. We applied this method to brain-tumors and observed brain metastases of breast cancer to have a ~2.5-fold reduction (p>0.05) in vessels/mm(2) compared to normal cortical regions. In contrast, vascular density in a glioma model was significantly higher (sections/mm(2) 736 ± 84; p<0.05). CONCLUSIONS: In summary, we present a vascular density counting method that is rapid, sensitive, and uses fluorescence microscopy without antibodies.